Estimating the Effects of Regulation When Treated and Control Firms Compete: A New Method with Application to the EU ETS - Geoffrey Barrows; Raphael Calel; Martin Jégard; Hélène Ollivier (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper presents a method for estimating treatment effects of regulations when treated and control firms compete on the output market. We develop a GMM estimator that recovers reduced-form parameters consistent with a model of differentiated product markets with multi-plant firms, and use these estimates to evaluate counterfactual revenues and emissions. Our procedure recovers unbiased estimates of treatment effects in Monte Carlo experiments, while difference-in-differences estimators and other popular methods do not. In an application, we find that the European carbon market reduced emissions at regulated plants without undermining revenues of regulated firms, relative to an unregulated counterfactual.
Keywords: Q48; L10; L50; 330; regulation; spillovers; environment; energy; firms